1983
DOI: 10.1002/tea.3660200708
|View full text |Cite
|
Sign up to set email alerts
|

A follow‐up power analysis of the statistical tests used in the Journal of Research in Science Teaching

Abstract: It has been two decades since the first power analysis of a psychological journal and 10 years since the Journal of Research in Science Teaching made its contribution to this debate. One purpose of this article is to investigate what power-related changes, if any, have occurred in science education research over the past decade as a result of the earlier survey. In addition, previous recommendations are expanded and expounded upon within the context of more recent work in this area. The absence of any consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This means that the significance tests employed had a 63% chance of detecting significant departures from the null hypothesis as large as 0.5 standard deviation units. Although a larger value for power is desirable, the obtained value of 0.63 is identical with the average power reported in a recent power analysis of 192 studies reported in JRST (Woolley and Dawson, 1983). To get a further indication of the power of the statistical tests, the obtained effect size for the study was computed using the pooled standard deviation for both samples (14.9) and the adjusted difference between sample means (7.8 points).…”
Section: Resultssupporting
confidence: 59%
“…This means that the significance tests employed had a 63% chance of detecting significant departures from the null hypothesis as large as 0.5 standard deviation units. Although a larger value for power is desirable, the obtained value of 0.63 is identical with the average power reported in a recent power analysis of 192 studies reported in JRST (Woolley and Dawson, 1983). To get a further indication of the power of the statistical tests, the obtained effect size for the study was computed using the pooled standard deviation for both samples (14.9) and the adjusted difference between sample means (7.8 points).…”
Section: Resultssupporting
confidence: 59%
“…Furthermore, published concerns about the misinterpretation of significance testing and published efforts to advocate alternatives have had little influence on actual practice (B. Thompson, 1997;Woolley & Dawson, 1983;Young, 1993). Several reviews of journals in these fields have confirmed this resistance to change in the use of signifi-cance testing (Dar, Serlin, & Omer, 1994;Kirk, 1996;Plucker, 1997;B.…”
mentioning
confidence: 99%
“…Relative to findings in the field of science teaching, ToP researchers were as likely to detect large or medium effects as were other researchers (e.g., Woolley & Dawson, 1983). Given Osborne et al's (2001) and findings that psychology teaching research results in a medium effect, ToP researchers appear just as likely to be able to detect effects as researchers teaching in other areas of science.…”
Section: Discussionmentioning
confidence: 68%
“…Comparable to findings in the field of psychology (e.g., Cohen, 1962;Rossi, 1990;Sedlmeier & Gigerenzer, 1989), ToP researchers more likely detected large than medium or small effects. In a secondary analysis, ToP researchers' power to detect effects was generally similar to teaching-related journals in other disciplines (e.g., Journal of Research in Science Teaching [JRST]) for medium and large effect sizes, but less for small effect sizes (e.g., Daly & Hexamer, 1983;Penick & Brewer, 1972;Woolley, 1983;Woolley & Dawson, 1983). For example, Woolley and Dawson (1983) used a two-tailed alpha of .05 for each hypothesis test in examining 192 articles published in JRST and found statistical power estimates of .23, .63, and .85, for small, medium, and large effects, respectively.…”
Section: Comparison With Other Power Studiesmentioning
confidence: 87%
See 1 more Smart Citation